Core needle biopsy in fibroepithelial tumors: predicting factors for phyllodes tumors - Reis, Yedda Nunes (2021)
OBJECTIVES: This study aimed to evaluate the clinical and imaging predictive factors for the diagnosis of phyllodes tumors in patients with inconclusive results from core needle biopsy (fibroepithelial lesions). METHODS: We retrospectively analyzed data of patients who underwent surgical excision of breast lesions previously diagnosed as fibroepithelial lesions. Numeric variables were analyzed using the Shapiro-Wilk and t-tests, and categorical variables were analyzed using the chi-square and Fisher’s exact tests. Multivariate logistic regression was performed to calculate odds ratios and detect predictive factors for the diagnosis of PT. RESULTS: A total of 89 biopsy samples were obtained from 77 patients, of which 43 were confirmed as fibroadenomas, 43 as phyllodes tumors, and 3 as other benign, non-fibroepithelial breast lesions. The mean tumor size was 3.61 cm (range, 0.8–10 cm) for phyllodes tumors and 2.4 cm (range, 0.8–7.9 cm) for fibroadenomas. The predictive factor for phyllodes tumor diagnosis was lesion size 43 cm (po0.001). CONCLUSION: Our data indicate that fibroepithelial lesions of the breast larger than 3 cm are more likely to be phyllodes tumors.